The Scoptic Epigrams of Lucillius - Kudulytė-Kairienė, Audronė (Literatūra, 2010)
Scoptic epigram, as a specific subgenre of Greek literature, flourished in the Roman Empire in the first century A. D. The most outstanding Greek poet of scoptic epigram was Lucillius, the epigrammatist of the first century A. D. Lucillius wrote for his protector Nero and tried to follow the taste of the emperor. His poems are based on jokes, poking fun, anecdotes. He ridiculed faults of people, made attacks on the shortcomings of the body, wrote parodies of dedicatory epigrams, etc. The stylistic and linguistic features of some epigrams on physical faults of people, on athletes, on women, etc. are analyzed in this article (more than 20 epigrams are translated into Lithuanian for the first time). A conclusion is made that the routes of the poetry of Lucillius can be found in the iambic poetry, in the old comedy as well as in the poetry of Theocritus. Parody, irony and exaggeration helped Lucillius to ridicule the epigrams of his predecessors and to satirize the world in which he lived. Despite the obviously hyperbolic nature his epigrams throw some flashlight on the social and cultural life context of the Roman Empire.